2020
DOI: 10.1007/s40820-019-0357-y
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Flower-Shaped CuO Nanostructures and Their Photocatalytic and Antibacterial Activities

Abstract: HIGHLIGHTS• Eugenol (4-allyl-2-methoxyphenol) extracted from O. sanctum leaves is used as a natural reducing agent for the synthesis of CuO nanoflowers (NFs).• CuO-NFs can degrade methylene blue with an efficiency of 90%. • CuO-NFs offer a new vision to deactivate multi-drug microorganisms. A B S T R AC T C o pper oxide nanoflowers (CuO-NFs) have been synthesized through a novel green route using Tulsi leaves-extracted eugenol (4-allyl-2-methoxyphenol) as reducing agent. Characterizations results reveal the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(62 citation statements)
references
References 74 publications
5
57
0
Order By: Relevance
“…The free radicals formed as a result of the reaction described above cause oxidative damage to the bacterial membrane ( Baldemir et al, 2017 ). Similar to our findings, in another study, application of 25 µg / mL eugenol-Cu hNF has been reported to have an inhibitory effect against Escherichia coli , Staphylococcus aureus and Pseudomonas fluorescens strains ( Sidduqui et al, 2020 ). Celik et al (2020) reported that the catalytic and antimicrobial activity of NFs depends on the Fenton mechanism and the morphology of NFs.…”
Section: Resultssupporting
confidence: 92%
“…The free radicals formed as a result of the reaction described above cause oxidative damage to the bacterial membrane ( Baldemir et al, 2017 ). Similar to our findings, in another study, application of 25 µg / mL eugenol-Cu hNF has been reported to have an inhibitory effect against Escherichia coli , Staphylococcus aureus and Pseudomonas fluorescens strains ( Sidduqui et al, 2020 ). Celik et al (2020) reported that the catalytic and antimicrobial activity of NFs depends on the Fenton mechanism and the morphology of NFs.…”
Section: Resultssupporting
confidence: 92%
“…Recently, Siddiqui et al synthesized copper oxide nanoflowers (CuO-NFs) and reported excellent performance for the degradation of methylene blue as well as inactivation of microorganisms ( E. coli ). 306 …”
Section: Antibacterial and Antiviral Properties Of Nanomaterialsmentioning
confidence: 99%
“…Flower shaped Copper Oxide Nanostructures obtained by Siddiqui et al [35] using O. sanctum and eugenol as capping agent exhibited Anti-microbial propensity against P vulgaris, P fluorescens, S. aureus and E. coli via agar diffusion method. E. coli exhibited maximum propensity when subjected to different concentrations ranging from 25 ug ml −1 to 100 ug ml −1 of Copper Oxide nanostructures using agar diffusion method.…”
Section: Anti-microbial Propensity and Toxicity Studiesmentioning
confidence: 99%
“…Green synthesis of Copper Oxide Nanoparticles using CuCl 2 .2H 2 O (Cupric Chloride dihydrate) and aqueous leaf extract of Malva sylvestris along with sodium hydroxide yielded Copper Oxide Nanoparticles of 5 nm to 30 nm as analysed by SEM [25]. Floral extract of Magnolia champaca [26] and leaf extract of O. Sanctum [35] (Tulsi leaves) with Eugenol as capping and stabilizing agent was used to prepare Copper Oxide Nanoparticles from copper acetate as starting material. Copper Oxide Nanoparticles with average crystalline size of 35±6 nm was obtained using the floral extract of Magnolia champaca [26] and were studied not only for its toxicity effect using DPPH ABST Test, but also evaluated for toxicity on aquatic life form using zebra fish embryos as study model [26].…”
Section: Synthesis and Characterization Of Copper Oxide Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation